Problems and Solutions for Testing Hemostasis Assays while Patients Are on Anticoagulants - Tripodi, Armando (Seminars in Thrombosis and Hemostasis, 2012)
Anticoagulant drugs affect directly or indirectly several coagulation parameters. This article is aimed at reviewing the problems encountered while testing patients on treatment and presents potential solutions. In general, it is recommended to postpone the performance of laboratory investigation upon discontinuation of the drug, preferably 2 days or more depending on the drug's half-life. If this strategy is unfeasible and patients remain on treatment, results of testing will likely be affected and result interpretation then requires great caution and knowledge of the peculiar and differential mechanism of action of the relevant anticoagulant drug being used.
Keywords: hemostasis assays; anticoagulant drugs; laboratory tests; heparins; vitamin K antagonists; direct inhibitors